OPTIMAL MANAGEMENT OF PLENGAN HIDROPOWER IN DAM SERI CIPANUNJANG-CILEUNCA BASE ON STOKASTIK DISKRIT MARKOV METHODE ON BANDUNG DISTRICT WEST JAVA - PRATAMA SARI (NIM : 25712301), IIN
Nowadays, There is unbalance situation between clean water demand and supply due to growth of population and industry. Water resource management need to be led to create synergy and integrity between the cross-areas, cross-sector, and cross-generation. This thesis discusses about intake Cikalong as water resource infrastructure supplying water for PDAM Bandung city and PDAM Bandung regency which depend on the operational of Cipanunjang dam - Cileunca dam, Plengan hydropower, Lamajan hydropower, Cikalong hydropower and water from Cisangkuy river. Today, capacity of PDAM Bandung city is 1800 L/sec and capacity of PDAM Bandung regency is 500 L/sec. However the amount of water that could be provided by PDAM Bandung city is 1400 L/sec while PDAM Bandung regency is 200 L/sec. Hence, Optimization on upstream infrastructure is needed to make sure the quantity of water is supplied enough. There are some methods that can be used to fulfill that aim, on this research use Stochastic Markov method. Base on findings of this study, the capacities of water required to fulfill allocation of R20 (95%) of SPAM demand are 578,63 L/sec of from Cipanunjang dam and 1216,84 L/sec from Ciluenca dam. there is minimum allocated water supply to fulfill continuity and concept water sharing in Cisangkuy Watershed